2022
DOI: 10.1186/s12882-022-02823-6
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of extracellular vesicles from hyperphosphatemia-stimulated endothelial cells provides insight into the mechanism underlying vascular calcification

Abstract: Background Hyperphosphatemia (HP) is associated with vascular calcification (VC) in chronic kidney disease (CKD). However, relationship between HP-induced-endothelial extracellular vesicles (HP-EC-EVs) and VC is unclear, and miR expression in HP-EC-EVs has not been determined. Methods We isolated HP-EC-EVs from endothelial cells with HP and observed that HP-EC-EVs were up-taken by vascular smooth muscle cells (VSMCs). HP-EC-EVs inducing calcium dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It is no coincidence that both research studies shared several common miRNAs: 7 miRNAs were up-regulated (miR-92b-5p, miR-204-3p, miR-296-3p, miR-494-3p, miR-667-5p, miR-702-5p, and miR-770-3p) while 6 miRNAs were down-regulated (let-7b-5p, miR-19b-3p, miR-24-3p, miR-30e-5p, miR-99b, and miR-199a-5p). Especially, miR-99b and miR-24-3p were decreased in VC condition in previous studies ( 104 , 159 ). It also suggested that Runx2 was controlled by miR-30e, and the downregulation of miR-30e indicated osteoblast differentiation regulation ( 175 ).…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Vs...supporting
confidence: 49%
See 2 more Smart Citations
“…It is no coincidence that both research studies shared several common miRNAs: 7 miRNAs were up-regulated (miR-92b-5p, miR-204-3p, miR-296-3p, miR-494-3p, miR-667-5p, miR-702-5p, and miR-770-3p) while 6 miRNAs were down-regulated (let-7b-5p, miR-19b-3p, miR-24-3p, miR-30e-5p, miR-99b, and miR-199a-5p). Especially, miR-99b and miR-24-3p were decreased in VC condition in previous studies ( 104 , 159 ). It also suggested that Runx2 was controlled by miR-30e, and the downregulation of miR-30e indicated osteoblast differentiation regulation ( 175 ).…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Vs...supporting
confidence: 49%
“…MiR-29b (miR-29b-3p) and miR-126-5p in EC-EVs also negatively regulated VC ( 102 , 103 ). Additionally, we detected the profile of miRNAs in HP-EVs from HUVECs by RNA-seq, finding that miR-3182 increased while 13 known miRNAs decreased in HP-EVs from HUVECs ( 104 ), indicating the potential function of miRNAs encapsulated in EC-EVs during VC.…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Ec...mentioning
confidence: 99%
See 1 more Smart Citation
“…And the combined use of miR-143 and miR-145 mimics was similar to the combined use of miR-221 and miR-222 inhibitors, which could more significantly block the aggravating effects of EV UR on CM-induced calcification [ 172 ]. For Hp-EC-EVs (hyperphosphatemia-induced-endothelial extracellular vesicles) miRNA-seq analysis showed that miRNAs expression were changed: 12 down-regulated miRs (has-miR193b-5p, hsa-miR-941, hsa-miR-99b-5p, hsa-miR-365a-5p, hsa-miR-30c-2-3p, hsa-miR-30a-3p, hsa-miR-30a-5p, hsa-miR-486-5p, hsa-miR-7706, hsa-miR-10a-5p, hsa-miR-10b-5p and including hsa-miR-143-3p as confirmed above) and an up-regulated hsa-miR-3182, suggesting that these miRs may be potential markers for CDK-VC; KEGG analysis of Top-20 signaling pathways showed that calcium signaling pathway, cAMP signaling pathway, and ABC transporters may be closely related to VC [ 261 ]. A recent study also shown that miR-670-3p released from ECs-EVs plays an important role in regulating VC and may be a potential target for arterial calcification in patients with CKD [ 68 ].…”
Section: The Crosstalk In Vascular Calcificationmentioning
confidence: 88%